HUBUNGAN AKTIVITAS FISIK DAN BODY IMAGE DENGAN STATUS GIZI SISWI SMA YAYASAN PUPUK KALTIM BONTANG - Prisilia, Cindy; Rachmi, Eva; Aminyoto, Meiliati (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
Nutritional status is a condition caused by a balanced between nutrient intake and nutritional requirements for metabolism. In Indonesia, the prevalence of overweight 15.1% and underweight 4.7%. This study aims to determine the relationship between physical activity and body image with nutritional status of students in senior high school of Yayasan Pupuk Kaltim Bontang. This study was an observational analytic with cross sectional study. The sampling procedure was purposive sampling according to the inclusion and exclusion criteria. The respondent of this study amounted to 262 students. The data collection being done with anthropometric measure to determine the nutritional status of students and using physical activity questionnaires to determine physical activity and body image questionnaires to determine body image. Based on bivariate analysis, there was no relationship between physical activity with nutritional status in senior high school students of Yayasan Pupuk Kaltim (p value = 1.00) and there was relationship between body image with nutritional status in senior high school students of Yayasan Pupuk Kaltim (p value = 0,000). There was 67.6% of students are normal nutritional status, 67.9% of students do moderate physical activity, and 56.5% of students with positive body image. There was not relationship between physical activity and nutrirional status and there was relationship between body image with nutritional status in senior high school students of Yayasan Pupuk Kaltim.